2014
DOI: 10.1186/2052-1847-6-21
|View full text |Cite
|
Sign up to set email alerts
|

A novel compression garment with adhesive silicone stripes improves repeated sprint performance – a multi-experimental approach on the underlying mechanisms

Abstract: BackgroundRepeated sprint performance is determined by explosive production of power, as well as rapid recovery between successive sprints, and there is evidence that compression garments and sports taping can improve both of these factors.MethodsIn each of two sub-studies, female athletes performed two sets of 30 30-m sprints (one sprint per minute), one set wearing compression garment with adhesive silicone stripes (CGSS) intended to mimic taping and the other with normal clothing, in randomized order. Sub-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 76 publications
(88 reference statements)
2
47
0
2
Order By: Relevance
“…The large number of outcomes analysed here (79 data-points) compared to previous meta-analyses (17 and 30 data points for the analyses of Hill et al and Marques-Jimenez et al, respectively) may further explain the conflict between results [6,33,38,47,[55][56][57][58][59][60][61][62]. As the recovery rates of these different movements are unique to their neuromuscular profiles [84,85], any positive impacts from CG which stem purely from attenuating muscle damage will vary according to outcome measures.…”
Section: Compression Power Recovery and Runningmentioning
confidence: 92%
See 2 more Smart Citations
“…The large number of outcomes analysed here (79 data-points) compared to previous meta-analyses (17 and 30 data points for the analyses of Hill et al and Marques-Jimenez et al, respectively) may further explain the conflict between results [6,33,38,47,[55][56][57][58][59][60][61][62]. As the recovery rates of these different movements are unique to their neuromuscular profiles [84,85], any positive impacts from CG which stem purely from attenuating muscle damage will vary according to outcome measures.…”
Section: Compression Power Recovery and Runningmentioning
confidence: 92%
“…For example, drawing valid conclusions on the effects of pressure was not possible, as only eight trials directly recorded compression pressures [21,35,36,53,55,59,62,63]. Finally, the large, very likely benefits reported for strength recovery at 2-8 h following resistance exercise [22] and for next-day cycling performance respectively [35] were both based on the results of single studies.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results have been mixed, and at times even conflicting. On the one hand, some studies have shown positive effects on performance, edema formation, and regeneration in runners, triathletes, and cyclists . There have also been somewhat positive effects with respect to vascular function, lactate removal, and leg volume, however, the athletes involved did not actively notice these effects, and they did not lead to any measurable performance gain .…”
Section: Introductionmentioning
confidence: 99%
“…Die Ergebnisse sind heterogen, teils widersprüchlich. So konnten einerseits positive Effekte auf Leistungsfähigkeit, Ödematisierung und Regeneration bei Läufern, Triathleten oder Radfahrern nachgewiesen werden . Teils waren positive Effekte auf die vaskuläre Funktion, den Laktatabstrom und das Beinvolumen messbar, die aber von den Sportlern nicht wahrgenommen wurden und zu keinem messbaren Leistungsgewinn führten .…”
Section: Introductionunclassified